Analysis on ceiling space radio wave propagation in indoor environment. Issue 11 (6th October 2020) - Sato, Yoshihito; Ishiyama, Ryo; Takeda, Shigeki
Abstract: In this paper, received power levels in 420 M/920 M/2.4G/5.3 GHz bands for sensor networks and WLANs are obtained by ray‐trace analysis in an office environment and the detail properties of propagation paths are analyzed. As a result, 25% average power of the total power arrives through ceiling spaces in the rooms where electromagnetic waves are hard to arrive through the walls. This means that the power remains in −6 dB even though the propagation paths are blocked by several metallic furniture beside the walls. In this indoor environment, the propagation paths through ceiling spaces can be relatively good for wireless communication. The results confirm that modeling of structures in ceiling spaces is necessary to obtain practical received power levels.